Representações surdas sobre a língua de sinais no Facebook - Belo, José Tiago Ferreira (Universidade do Vale do Rio dos Sinos, 2016)
This dissertation presents an analysis of representations that the deaf do on the sign language from the social network Facebook. For that, the reflections of Stuart Hall, mainly those related to the constitution of the cultures and the representation, were taken as base. From these reflections, the concept of representation was used as a theoretical-methodological tool. In this way, publications were analyzed in groups and Facebook pages with a high concentration of deaf people. These publications by the deaf appear in the form of posts or comments, in Brazilian sign language or in written Portuguese, containing public testimonies of deaf Facebook users. Based on the analysis of the material, made up of videos, texts and images shared on Facebook, it was noticed that the importance given to sign language by deaf people has been represented as an icon of a visual community; As a synonym for Deaf identity; As a deaf tongue itself; As an instrument of accessibility; As a Brazilian language; And as a possibility of deaf empowerment. The deaf have still generated more contact between them from the use of Facebook, strive to find more technologies in this social network, from the use of audiovisual media in which it is possible to register the sign language, as well as through applications Online conversation within Facebook.
Keywords: Língua de sinais; Educação de surdos; Cultura surda; Representação; Facebook; Sign language; Deaf education; Deaf culture; Representation; Facebook; ACCNPQ::Ciências Humanas::Educação